Financial Inclusion Across Asia : Bringing Opportunities for Businesses - Leong, Choi Meng (Emerald Publishing Limited, 2023)
The term financial inclusion describes an individual’s ability to obtain effective and inexpensive financial products and services that match their demands, whilst extending to include businesses access to finances to enable planning for long-term goals or unpredictable emergencies. This allows micro, small, and medium-sized businesses to access financial products on a sustainable basis for a reasonable price. Financial Inclusion Across Asia provides thought-provoking studies centred around Asia and the United Nations Sustainable Development Goals (SDGs).